Green Procurement Practices and Barriers in Furniture Manufacturing Companies - Shiau Wei Chan; S. T. Suman Tiwari; M.F. Ahmad; Izzuddin Zaman; Wan Ling Sia (International Journal of Supply Chain Management, 2018)
Lack of awareness is the most significant barrier to implementing green procurement practices among procurement managers. Procurement managers seldom consider the effects of procurement on the environment. This situation will cause many environmental problems such as carbon dioxide emissions, climate change, greenhouse effects, pollution, and deforestation. Hence, the purpose of this study is to identify the current practices of green procurement in furniture manufacturing companies. Additionally, this study intends to determine barriers to green procurement practices in furniture manufacturing companies. In this study, 118 procurement officers and managers were chosen randomly from furniture manufacturing companies in Batu Pahat, Johor. This study applied a quantitative method and utilized the Statistical Package Social Science (SPSS) version 20.0 to analyse the data from the responses of questionnaires. Descriptive analysis was employed to achieve the research objectives. The findings of this study have revealed that current practices of green procurement in furniture manufacturing companies include ensuring the safe, incoming movement of product to facilities, followed by ensuring that suppliers locations are operated in a safe manner. Meanwhile, the main barrier to green procurement practices is that procedures for the implementation of green procurement are time-consuming. This study is important for furniture manufacturing companies to use green procurement practices in their operation and production processes.